2014
DOI: 10.1074/jbc.m114.578179
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-converting Enzyme 1 and β-Arrestins Exert Spatiotemporal Control of Substance P-induced Inflammatory Signals

Abstract: Background: Agonists stimulate the subcellular redistribution of receptors. The importance of trafficking for pathophysiological processes is unknown. Results: Substance P inflammatory signaling required receptor interaction with ␤-arrestins and endothelin-converting enzyme, which mediated endocytosis and recycling. Conclusion: Sustained substance P inflammatory signaling requires receptor recycling. Significance: Mechanisms that maintain receptors at the cell surface are necessary for sustained signaling by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…2G and fig. S3E), which also depends on βARRs and PKC but not on epidermal growth factor receptor transactivation (9, 22, 23). UBO-QIC, the phospholipase C (PLC) inhibitor U73122, and the Ca 2+ chelator EGTA prevented activation of cytosolic PKC (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2G and fig. S3E), which also depends on βARRs and PKC but not on epidermal growth factor receptor transactivation (9, 22, 23). UBO-QIC, the phospholipase C (PLC) inhibitor U73122, and the Ca 2+ chelator EGTA prevented activation of cytosolic PKC (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We have previously shown that βARRs mediate NK 1 R endosomal signaling and nuclear ERK activation (9, 22, 23). To examine the contribution of G proteins to endosomal NK 1 R signaling, we used BRET to study SP-induced trafficking of Gα q subunits to early endosomes containing RAB5A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of [Ca 2ϩ ] i -HEK293, KNRK-PAR 2 -Kaede, or NCM460 cells were loaded with Fura-2/AM (1 M, Invitrogen) in assay buffer (150 mM NaCl, 2.6 mM KCl, 0.1 mM CaCl 2 , 1.18 mM MgCl 2 , 10 mM D-glucose, 10 mM HEPES, pH 7.4) containing 4 mM probenecid and 0.5% BSA for 1 h at 37°C (12). Fluorescence was measured at 340 and 380 nm excitation and 530 nm emission using a FlexStation III microplate reader (Molecular Devices, Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
“…For some receptors, for example the substance P neurokinin 1 receptor, the calcitonin gene-related peptide receptor, and the -opioid receptor, recycling of internalized receptors is the main pathway for replenishing the plasma membrane. For these receptors, ligand dissociation and degradation in acidified early endosomes, and receptor dissociation from ␤-arrestins, are key events controlling recycling (11)(12)(13)(14)(15). Other receptors traffic to degradation pathways, and here the synthesis of new receptors or the mobilization of intracellular pools of fresh receptors is required for replenishment of the plasma membrane.…”
mentioning
confidence: 99%